Increasing the Marketing of Cepoko Village MSMEs Through Digital Marketing Seminar - Fifi Aidillia Ruhillah; M. Zaki Mubarok Wafiyullah; Ahmad Zainal Abidin; Dina Nas’atul Hidayah; Adib Al Majid; Imam Lutfi Prasetya Budi; Tiara Agustien (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
In the increasingly evolving digital era, digital marketing is an important element for businesses to build brand awareness, increase sales, and expand market reach. By using various online platforms such as social media, search engines, email, and websites, companies can reach consumers directly, provide relevant content, and monitor and analyze campaign results in real-time. Cepoko Village, Gunungpati District, Semarang City, is one of the areas that has many MSME actors with quality products. However, most of them still experience obstacles in marketing their products. This seminar was carried out through two steps, namely observation and interviews where we collected data obtained from the head of RT, the head of MSMEs, and several MSME actors in Cepoko village. The next step is to arrange a seminar by bringing in speakers to provide an explanation of digital marketing at the Cepoko Village Hall.The purpose of holding this seminar is to provide insight to Cepoko Village MSMEs on how to market digital marketing and look for business opportunities in social media.